Writing Strategies Used by Indonesian EFL Undergraduate Students across Their Proficiency and Gender - Ardila, Istiqamah (Journal of Language Intelligence and Culture, 2020)
Proficient writers in L2 setting used many kinds of strategies to face their difficulties in English writing. This study investigates the writing strategies used by Indonesian EFL undergraduate students and examines if there is any differences between proficient and less proficient students across their gender in choosing strategies in writing. The subject of the study consisted of 100 (one hundred) undergraduate students of English Department in Islamic State University of Antasari, Banjarmasin. A questionnaire was adopted from Peñuelas (2012) to gather data about student writing strategies. The categorization of proficient and less proficient of the students was based on the result of writing test. The results indicated that Indonesian EFL undergraduate students used six categories of writing strategies and compensation strategies was the most frequently used followed by affective strategies as the least frequently used. Proficient and less proficient students employed compensation strategies as the dominant strategies both male and female students. The differences of strategies used based on students gender did not occur in proficient students. However, the differences was significant of less proficient male and female students only in affective strategies while the rest was not significant. Furthermore, proficient female students used more strategies than male in term of categories while less proficient male used more strategies in memory and compensation strategies than female.